Management of psoriatic arthritis: a consensus opinion by expert rheumatologists - D’Angelo, Salvatore; Atzeni, Fabiola; Benucci, Maurizio; Bianchi, Gerolamo; Cantini, Fabrizio; Caporali, Roberto Felice; Carlino, Giorgio; Caso, Francesco; Cauli, Alberto; Ciccia, Francesco; D’Agostino, Maria Antonietta; Dagna, Lorenzo; et al. (Frontiers in Medicine, 2023)
Background Psoriatic arthritis (PsA) is a chronic inflammatory musculoskeletal disease involving several articular and extra-articular structures. Despite the important progresses recently made in all of the aspects of this disease, its management is still burdened by unresolved issues. The aim of this exercise was to provide a set of statements that may be helpful for the management of PsA. Methods A group of 38 Italian rheumatologists with recognized expertise in PsA selected and addressed the following four topics: “early PsA,” “axial-PsA,” “extra-articular manifestations and comorbidities,” “therapeutic goals.” Relevant articles from the literature (2016–2022) were selected by the experts based on a PubMed search. A number of statements for each topic were elaborated. Results Ninety-four articles were selected and evaluated, 68 out of the 1,114 yielded by the literature search and 26 added by the Authors. Each of the four topic was subdivided in themes as follows: transition from psoriasis to PsA, imaging vs. CASPAR criteria in early diagnosis, early treatment for “early PsA”; axial-PsA vs. axialspondyloarthritis, diagnosis, clinical evaluation, treatment, standard radiography vs. magnetic resonance imaging for “axial PsA”; influence of inflammatory bowel disease on the therapeutic choice, cardiovascular comorbidity, bone damage, risk of infection for “comorbidities and extra-articular manifestations”; target and tools, treat-to-target strategy, role of imaging for “therapeutic goals.” The final document consisted of 49 statements. Discussion The final product of this exercise is a set of statements concerning the main issues of PsA management offering an expert opinion for some unmet needs of this complex disease.